Faktor-Faktor Keberhasilan Strategy Execution dalam Organisasi Pelayanan Kesehatan: Literature Review - Salsabila Firdausi; Tuanku Banang Rabbani Imsyaamru; Acim Heri Iswanto (CENDEKIA : Jurnal Penelitian dan Pengkajian Ilmiah, 2026)
Healthcare organizations face challenges in improving service quality, patient safety, operational efficiency, and the ability to adapt to change. An organization’s success depends not only on strategic planning but also on the effectiveness of strategy execution. This study aims to identify and summarize the factors influencing the success of strategy execution in healthcare organizations. The method used was a literature review by searching scientific articles from Google Scholar, PubMed, ScienceDirect, and Frontiers using relevant keywords. A total of ten articles meeting the inclusion criteria were analyzed narratively. The findings indicate that the success of strategy execution is influenced by effective leadership, organizational readiness, human resource management, infrastructure and technology support, a quality-oriented organizational culture, change management, and collaboration among units and stakeholders. Leadership plays a role in guiding strategy implementation and building readiness for change, while a quality-oriented culture and collaboration support continuous improvement. It is concluded that the synergy between leadership, organizational readiness, a quality-oriented culture, change management, and collaboration is a key factor in improving service quality, organizational efficiency, and patient satisfaction.